Evaluation of Maximal Reliability for Unidimensional Measuring Instruments With Correlated Errors. Issue 1 (2nd January 2017) - Gabler, Siegfried; Raykov, Tenko
Abstract : A latent variable modeling method for studying maximal reliability of unidimensional multicomponent measuring instruments with correlated errors is outlined. In the presence of correlation between 2 residual terms, the procedure allows one to point and interval estimate the reliability of the linear combination of the scale components that possesses the highest possible reliability coefficient. The approach is readily applicable with popular latent variable modeling software and also provides an alternative scoring rule to the widely used overall sum score for homogeneous psychometric scales. The discussed method is illustrated with a numerical example.